On the Border of the Syrian Refugee Crisis: Views From Two Different Cultural Perspectives. (April 2018) - Dimitrova, Daniela V.; Ozdora-Aksak, Emel; Connolly-Ahern, Colleen
Since the Syrian refugee crisis represents the worst humanitarian crisis in modern history, it is critical to examine how global media covered this issue. Focusing on two nations significantly affected by the refugee crisis—Bulgaria and Turkey, this study employs a content analysis to examine differences in refugee portrayals in national media. The results show that Turkish media coverage was more personalized and more likely to emphasize the victim frame. In contrast, Bulgarian coverage was less personalized and more likely to emphasize the administrative frame. The findings are placed within national context and their implications for media framing of refugees are discussed.